2005
DOI: 10.1097/00126450-200501000-00011
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Examination of Formal and Informal Mentoring Among Nurses

Abstract: This article focuses on how mentoring among nurses can help them to better serve their profession and health care organizations to more successfully achieve their goals. Specifically, it addresses how formal and informal mentoring can yield benefits to both the nursing profession and health care organizations. It presents some advantages and disadvantages of formal and informal mentoring. Finally, it delineates some important considerations that should be carefully analyzed before establishing a formal program. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 6 publications
3
60
0
1
Order By: Relevance
“…At the core of the relationship are two people who see value and meaning in eachother and want to be in a relationship together [13,49,50]. Barker [42] and Young [45] describe mentoring as a relationship that is based on mutual respect and common goals.…”
Section: Characteristics Of Mentoringmentioning
confidence: 99%
See 1 more Smart Citation
“…At the core of the relationship are two people who see value and meaning in eachother and want to be in a relationship together [13,49,50]. Barker [42] and Young [45] describe mentoring as a relationship that is based on mutual respect and common goals.…”
Section: Characteristics Of Mentoringmentioning
confidence: 99%
“…Mentors are approachable, knowledgeable, honest, friendly, patient, experienced, enthusiastic, and willing to spend time with the mentee [10,15,17,43,44,47,50,52,53]. Mentors have astrong belief in the mentee's capability [13,18]; they challenge, support, and encourage a mentee [54][55][56].…”
Section: Characteristics Of Mentoringmentioning
confidence: 99%
“…The transformation of a mentoring relationship into friendship is discussed only in the context of informal mentoring (Ryan et al, 2010;Simpson, 2005;Tourigny & Pulich, 2005). However, findings from this study suggest that well designed formal mentoring relationships can result in friendship.…”
Section: Discussionmentioning
confidence: 83%
“…For participating NPs the mentoring relationship does not seem to end, but rather transforms into a personal and professional friendship. Based on these characteristics, mentoring relationships described by participants are more aligned with informal mentoring (Ryan, Goldberg, & Evans, 2010;Simpson, 2005;Tourigny & Pulich, 2005). In her 1998 study, Heyes found a significant difference in mentoring scores between students who were assigned mentors and those who chose the mentors themselves, suggesting that informal mentoring is more beneficial.…”
Section: Theory Of Mentoring For Nurse Practitioners In a Hospital Sementioning
confidence: 99%
“…[13] Tourigny and Pulich reported that mentoring facilitates development of tacit knowledge which includes innovative and creative thinking, intuitive knowing, and personal growth all of which are positive attributes for nurses and nursing students to develop (2005). [14] 1.1 Current body of knowledge -peer mentorship programs Previous studies are dated and explored peer mentorship programs within nursing education with the focus on the clinical setting and more precisely within medical/surgical units tied to single nursing courses. [15] The nursing education experience of nursing students is significantly different than that of students in non health academic programs.…”
Section: Introductionmentioning
confidence: 99%